Laotian Refugees in a Small-Town School: Contexts and Encounters - Tom Schram (Journal of Research in Rural Education, 1993)
I present a case study drawn from a two-year ethnographic study of Laotian adolescents in a rural New England school district where refugee resettlement has emerged as a factor of local socialchange. I describe how formal classroom encounters betweenLaotian students, their American peers, and theirteacher wereinfluenced by the community context and by a school culture in which tracking served as the organizational framework shaping the behavioral and instructional options of teachers and students. Particular attention is directed toward patterns of dependence and resistance that emerged, often unexpectedly, between culturally diverse student groups, and the ways in which the teacher mediated this interaction. My analysis highlights linkages betweenperceptions of competence and peer worth, the teacher's role in the social organization of work-related talk in the classroom, and the constraints and benefits peculiar to the small school setting.